"It's about respect!" college-athlete activism and left neoliberalism. Issue 4 (2nd October 2017) - Tompkins, Joe
ABSTRACT: This essay offers a critique of left neoliberalism with reference to certain tendencies in cultural studies, antiracist politics, disparity discourse, and college sports. Where the dominant tendency in cultural studies has been to produce complex analyses of identity-based oppression, this article insists on a conception of class politics that, on the one hand, calls for more attention to exploitation and, on the other, de-emphasizes the "working-class identity" model. By examining two recent episodes of athlete activism in college sports—namely, the much-admired "strike against racism" at the University of Missouri in 2015 and the widely condemned (and ultimately unsuccessful) effort by Northwestern University football players to form a union in 2014—the article contends that the commitment to eliminating racism and indifference to ending exploitation in these contexts reflects the broader commitments of a "left-wing" neoliberalism that devotes itself to ending inequality without redistributing wealth.